O espiritismo e a arte médica - Rezende, Eliane Garcia (2012)
As a socio-historical and cultural product, religion is a strategy for understanding man s social nature. Its cultural practice involving symbols and meanings, and constructing senses to life, usually plays an organizing role in diseased states. This way, we engaged in studying Spiritism and its explicability in illness and healing processes. Our aim was to identify, in spiritist literature, the concept of the health/ disease process, and analyze the health point of view and the professional practice of spiritist physicians and psychologists working at the Associação Médico-Espírita de Minas Gerais (AMEMG). The research followed qualitative premises, with recorded interviews and information saturation criteria in order to define the number of participants. There were ten interviewees, five from each professional category. In Brazil, Spiritism presents a perspective of spiritualized science , with doctors proposing the paradigm physician-spiritist . It is relevant to study how these professionals perform their Medical Art grounded upon this religious movement, which is also self-denominated as philosophical and scientific. The supportive bases for this reasoning are substantiated by Clifford Geertz, Peter Berger and Pierre Bourdieu. The explicability produced by Spiritism presents the law of action/ reaction as a guide-line, imputing to the individual the responsibility for his troubles, sorrows and diseases linked to his reincarnation. The perspective health/ disease drifts apart from the point of view of conventional medicine ; here, spirituality applied to social life will enable the healing process, which will not happen in a ritual dissociated from the patient s participation. Therefore, the occurring change is the signification capable of giving sense to sufferance and reintegrating it in a non measured biography for the length of one life. The AMEMG professionals perceive the process health/ disease and perform their Medical Art according to the doctrine codified by Allan Kardec in France, added to psychographies performed in Brazil, mainly those by Chico Xavier. The AMEMG offers the opportunity of a hybrid therapeutic space where conventional medicine and parallel medicine act together